PEMAHAMAN MATERI PEMBELAJARAN DALAM SISTEM SKS DI SEKOLAH MAN 1 MEDAN - Sani Susanti; Husna Harahap, Hidayatul; Jeni Pebrianti Rambe; Salsabila Adnin Daulay; Desy Novita Berutu (ISTIQRA: Jurnal Hasil Penelitian, 2024)
The learning system is a structure and process used in delivering material in the form of knowledge, skills, and morals to students. The learning system is an effort made by educators to shape the character and insight of students in the learning process. The learning system is closely related to the understanding of the material. The research method used is qualitative, involving data collection techniques in the form of observation and interviews. The data collected is then analyzed inductively by identifying patterns, themes, and concepts that emerge from the data. The purpose of this literature is to determine the effect of the learning system on students' understanding of the material. The results of this study indicate that the learning system implemented by MAN 1 Medan School is good, but some students are not yet compatible with the existing learning system. The learning system that is set greatly influences the understanding of the material absorbed by students. The implications of this study are expected that teachers can first adjust the learning system to the abilities of their students